Elimination of light-induced degradation at the nickel oxide-perovskite heterojunction by aprotic sulfonium layers towards long-term operationally stable inverted perovskite solar cells. Issue 11 (23rd September 2022) - Wu, Tianhao; Ono, Luis K.; Yoshioka, Rengo; Ding, Chenfeng; Zhang, Congyang; Mariotti, Silvia; Zhang, Jiahao; Mitrofanov, Kirill; Liu, Xiao; Segawa, Hiroshi; Kabe, Ryota; Han, Liyuan; et al.
Abstract : This work introduces an aprotic sulfonium buffer layer at the nickel oxide–perovskite heterojunction to eliminate the multi-step photochemical reactions, which leads to inverted perovskite solar cells with long-term operational stability. Abstract : Nickel oxide (NiO x ) is a promising hole-selective contact to produce efficient inverted p-i-n structured perovskite solar cells (PSCs) due to its high carrier mobility and high transparency. However, the light-induced degradation of the NiO x –perovskite heterojunction is the main factor limiting its long-term operational lifetime. In this study, we used the time-resolved mass spectrometry technique to clarify the degradation mechanism of the NiO x -formamidinium–methylammonium iodide perovskite (a common composition for high-performance PSCs) heterojunction under operational conditions, and observed that (1) oxidation of iodide and generation of free protons under 1-sun illumination, (2) formation of volatile hydrogen cyanide, methyliodide, and ammonia at elevated temperatures, and (3) a condensation reaction between the organic components under a high vapor pressure. To eliminate these multi-step photochemical reactions, we constructed an aprotic trimethylsulfonium bromide (TMSBr) buffer layer at the NiO x /perovskite interface, which enables excellent photo-thermal stability, a matched lattice parameter with the perovskite crystal, and robust trap-passivation ability. Inverted PSCs stabilized with the TMSBr buffer layer reached the maximum efficiency of 22.1% and retained 82.8% of the initial value after continuous operation for 2000 hours under AM1.5G light illumination, which translates into a T 80 lifetime of 2310 hours that is among the highest operational lifetimes for NiO x -based PSCs.